COMMUNICATION STRATEGY OF DPC PDI PERJUANGAN SURABAYA IN WINNING VOTES IN THE 2024 LEGISLATIVE ELECTIONS - Tarmuji, Tarmuji (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to find out how the political communication strategy of a party, especially the Indonesian Democratic Party (PDI) of Struggle in Surabaya, which in the 2019 legislative elections (pileg) managed to get 463,695 votes or around 32.30 per cent of the total voters. However, the dynamics of national politics ahead of the 2024 Presidential election made a big change to the political order. Where President Joko Widodo, who is a PDIP cadre, indirectly provides support to non-PDIP Presidential Candidates. The data collection technique is natural setting (natural conditions), primary data sources, and data collection techniques are more on participant observation, in-depth interviews and documentation. The result of this research is that PDI Perjuangan Surabaya in gaining votes in the 2024 legislative election uses a communication strategy with various communication channels to disseminate information, programmes, ideas and influence. The channels used include conventional media, online media and social media. In addition, one of PDIP's communication styles is going down to the community. The involvement and strengthening of the three pillars of the party, namely the DPC PDIP management, party officers in the executive and party officers in the legislature is another strategy. DPC PDIP Surabaya also involves young people in its communication strategy. There are PDIP Surabaya figures who have great influence in the city of Surabaya such as former Mayor Bambang DH, former Mayor Tri Rismaharini and the granddaughter of the Indonesian Proclamator, Puti Guntur Soekarno.